Barriers and strategies of hydrogen fuel cell power generation based on expert survey in South Korea - Lee, Youhyun; Lee, Min Chul; Kim, Young Jin (International Journal of Hydrogen Energy, 2022)
Recently, South Korea has become a pioneer in implementing hydrogen fuel cell energy production; however, sustainable development of hydrogen fuel cell as an energy source in South Korea remains limited. Hence, it is necessary to address these challenges that hinder such development. This study aims to identify the barriers to developing hydrogen fuel cell energy in South Korea and classify them. We used the combined qualitative methodology, which includes both expert Delphi surveys and Analytic Hierarchy Process techniques. Five factors were identified, each of which has three sub-factors derived for the Delphi survey. The results show that the most serious barriers are institutional and political factors; in addition, the cost of the unit and infrastructure of the fuel cell are significant barriers.
Keywords: Delphi surveys; Delphi-AHP; Fuel cell generations; Fuel cell power generation; Hydrogen Energy; Hydrogen fuel cell generation; Hydrogen fuel cells; Hydrogen policy; Korean hydrogen energy; South Korea; Delphi-AHP; Hydrogen fuel cell generation; Hydrogen policy; Korean hydrogen energy